The Effects of Angry Expressions and Fearful Expressions on Duration Perception: An ERP Study - Yin, Huazhan; Cui, Xiaobing; Bai, Youling; Cao, Gege; Zhang, Li; Ou, Yuhong; Li, Dan; Liu, Jinping (Frontiers in Psychology, 2021)
Little is known about the electrophysiological basis of the effect of threat-related emotional stimuli with different motivational direction on duration perception. Thus, event-related potentials were employed to examine the effects of angry expressions and fearful expressions on perception of different duration (490–910 ms). Behavioral results showed there was a greater underestimation of the duration of angry expressions (approach-motivated negative stimuli) than fearful expressions (withdrawal-motivated negative stimuli), compared with neutral expressions. Event-related potentials results showed that, the area of Contingent Negative Variation (CNV) evoked by angry expression, fearful expression and neutral expression gradually increased. These results indicated that specific electrophysiological mechanisms may underlie the attention effects of angry and fearful expressions on timing. Specifically, compared with neutral expressions, fearful expressions and angry expressions both are likely to distract more attentional resources from timer, in particular, angry expressions attract more attention resources than fearful expressions from timer. The major contribution of the current study is to provide electrophysiological evidences of fear vs. anger divergence in the aspect of time perception and to demonstrate beyond the behavioral level that the categorization of threat-related emotions should be refined so to highlight the adaptability of the human defense system.